2017
DOI: 10.18240/ijo.2017.12.07
|View full text |Cite
|
Sign up to set email alerts
|

Anterior lamellar recession for management of upper eyelid cicatricial entropion and associated eyelid abnormalities

Abstract: Based on the principles of lamellar recession and concurrently addressing the associated lid problems, this approach is an effective and safe treatment of UCE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“… 9 Few studies present the effect of modifications to this procedure in trachomatous entropion and trichiasis. 10 Because trachoma is common in our country, there is a probability that the number of surgeries for TT will rise. 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 Few studies present the effect of modifications to this procedure in trachomatous entropion and trichiasis. 10 Because trachoma is common in our country, there is a probability that the number of surgeries for TT will rise. 5 …”
Section: Introductionmentioning
confidence: 99%
“…9 Few studies present the effect of modifications to this procedure in trachomatous entropion and trichiasis. 10 Because trachoma is common in our country, there is a probability that the number of surgeries for TT will rise. 5 In the present study, we aimed to assess the combination of anterior lamellar recession with blepharoplasty, suprasternal fixation, and internal eyelash bulb extirpation of aberrant lashes posteriorly located in patients with any grade of upper eyelid trachomatous cicatricial entropion.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, excess skin and muscle removal through blepharoplasty have been recommended to prevent downward migration of the anterior lamella and provide a less bulky eyelid. [ 2 3 4 ] And finally, lid crease formation with bites through the levator helps maintain an upward vector of traction to the anterior lamella and lash eversion. [ 5 ]…”
mentioning
confidence: 99%
“…showed that out of 97 eyelids with upper lid cicatricial entropion, 18 patients underwent upper lid retractor recession with good results. [ 2 ] Barr et al . assumed that the high recurrence rate observed (21%) in their study following anterior lamellar recession was due to not performing concurrent levator recession.…”
mentioning
confidence: 99%